Multicenter trial of the proficiency of smart quantitative sensation tests. Issue 5 (28th January 2014) - Dyck, Peter J.; Argyros, Barbara; Russell, James W.; Gahnstrom, Linde E.; Nalepa, Susan; Albers, James W.; Lodermeier, Karen A.; Zafft, Andrew J.; Dyck, P. James B.; Klein, Christopher J.; Litchy, William J.; Davies, Jenny L.; et al.
ABSTRACT Introduction: We assessed proficiency (accuracy and intra‐ and intertest reproducibility) of smart quantitative sensation tests (smart QSTs) in subjects without and with diabetic sensorimotor polyneuropathy (DSPN). Methods: Technologists from 3 medical centers using different but identical QSTs independently assessed 6 modalities of sensation of the foot (or leg) twice in patients without (n = 6) and with (n = 6) DSPN using smart computer assisted QSTs. Results: Low rates of test abnormalities were observed in health and high rates in DSPN. Very high intraclass correlations were obtained between continuous measures of QSTs and neuropathy signs, symptoms, or nerve conductions (NCs). No significant intra‐ or intertest differences were observed. Conclusions: These results provide proof of concept that smart QSTs provide accurate assessment of sensation loss without intra‐ or intertest differences useful for multicenter trials. Smart technology makes possible efficient testing of body surface area sensation loss in symmetric length‐dependent sensorimotor polyneuropathies. Muscle Nerve49: 645–653, 2014